Scattering of positronium by H, He, Ne, and Ar - Biswas, P. K.; Adhikari, S. K. (Elsevier B.V., 2000)
The low-energy scattering of the ortho-positronium (Ps) by H, He, Ne, and Ar atoms has been investigated in the coupled-channel framework by using a recently proposed time-reversal symmetric non-local electron-exchange model potential with a single parameter C. For H and He, we use a three-Ps-state coupled-channel model and, for Ar and Ne, we use a static-exchange model. The sensitivity of the results is studied with respect to the parameter C. Present low-energy cross-sections for He, Ne and Ar are in good agreement with experiment. (C) 2000 Elsevier B.V. B.V. All rights reserved.